Atikian building, circa 1951 (1951)
Clipping with the caption: 'Distinctive architecture - Beautifully designed is the new Atikian Building on South Palm Canyon Drive. It is one of the many notable designed by William F. Cody, prominent local architect. Mr. Cody, member of the American Institute of Architects, has to his credit such handsome homes as those of Wm. Perlberg and Dorothy Levin, and among commercial buildings, new structures at Thunderbird Ranch and the Del Marcos Hotel.'